Influência de lâminas de irrigação sobre a produtividade da rebrota de Hemarthria altíssima - Santos, Karine Lançanova dos (2009)
The uses of the natural or cultivated grassland can be considered an important vital productivity possibility to the cattle raising holding in many different places in the world, where farmers who have cattles, sheeps, and other herbivorous species that have it as the mainly kind of food to feed their herds. So, the mainly purpose of this job was to evaluate the dry substance and the nutritional value of the Hemarthria altíssima (Poir) Stapf et C. E. Hubb, when it was submitted to the influences of the different water depth and the time of the break. This job was accomplished in land conditions, in the experimental area from the Universidade Regional Interada do Alto Uruguai e das Missões , Santiago, RS, during the period of de November/2007 to May/2008. The grass was stablished in the experimental area in September, 2005. The irrigation manner used, was based in a pre-established period of irrigation, with 7 days of break. It was tested four irrigation treatments, Treatment 1- without irrigation (witness), Treatment 2 7,5 layer mm h-1 , Treatment 3 layer of 15 mm h-1 and Treatment 4 layer of 22,5 mm h-1 , in each treatment it was analyzed the regrowth in breaks of 21,35 and 60 days. During each break it was accomplished a cut in a height about 7cm, after the samples were transported to the Bromatology Lab where they were desiccated in an air incubator with 60ºC with the constant weight, it permitted to determine the dry substance (MS). After fixing the dry substance, it was accomplished a chemistry analyses to fix the crude protein (PB), detergent fiber (FND), acid detergent fiber (FAD). The research results analyses were accomplished by statistical analysis of regression. For analysis of the results relating the cutting blade and irrigation were performed by means of the Scott-Knott test, the 5% of significance to compare with the medium. Though not always significant, the water layer increased the dry substance, and the biggest space of the cut, the biggest was the dry substance production, and the biggest was the percentages of FND and FAD . The smallest space among the cuts caused an increase in the PB . The obtained results in the conditions that the research was accomplished, can permit to concluded that the Grass Hemarthria altíssima was considered more efficient to the dry substance kg ha -1, it happened in a bigger cut space (60 days) and a smaller irrigation leyer (22, mm).